Formulasi Gel Ekstrak Daun Kelor (Moringa oleifera Lamk) Sebagai Sediaan Antiinflamasi - Sugihartini, Nining; Jannah, Syauqul; Yuwono, Tedjo (UI Scholars Hub, 2020)
The development of anti-inflammatory gel of Moringa oleifera leaf extract has been performed. This study aimed to determine the physical properties, irritation index and anti-inflammatory activity of gel with various concentration of Moringa oleifera leaf extract. The extract was obtained by maceration method using ethanol 70%. The extracts were formulated in a gel with a concentration of 3%, 6%, 9% by using Carbopol 940 as gelling agent. The gel was evaluated for its physical properties (viscosity, pH, spreadability, adhesivity), irritation index with rabbit test animals and anti-inflammatory activity with mice test animals based on epidermal thickness parameters. The test results showed that the increasing of extract concentration changed the viscosity, pH, adhesivity, epidermal thickness and spreadability of the gel. Based on the results of this study it can be concluded that the optimum concentration of Moringa oleifera leaf extract in gel as anti-inflammatory was 3%.